The Need for a Global Ocean Vision Within Biodiversity Beyond National Jurisdiction: A Key Role for Strategic Environmental Assessment - Ferreira, Maria Adelaide; Johnson, David E.; Andrade, Francisco (Frontiers in Marine Science, 2022)
Strategic Environmental Assessment (SEA) is written into the draft Legally Binding International Agreement for the conservation and sustainable use of biodiversity beyond national jurisdiction (BBNJ). But what does that mean and what could it mean? This perspective argues that a future vision for the global ocean, encompassing ocean health and productivity, ecosystem integrity and resilience, together with social equity, and including area beyond national jurisdiction, is fundamental – one which is holistic and universally accepted to guide future ocean policies, plans and programmes (PPPs). We suggest SEA as the best available tool to develop such a vision and its utility for this purpose should be recognised at BBNJ. This perspective paper first justifies why such a Global Ocean Vision is essential. It then describes the key characteristics any vision must integrate and how it can be elaborated in the framework of a collective SEA. To reap its full potential to create a vision for the 21st century and beyond, to guide a sustainable ocean economy, this perspective paper concludes that the Environmental Impact Assessment (EIA) roots and current common understanding of SEA must be re-evaluated and replaced by a truly strategic approach. Particularly for remote parts of the ocean, where information is lacking, strategy-based (proactive) SEA must move beyond requiring different instruments to meet set criteria. We advocate expanding text in Part I General Provisions of the draft BBNJ Agreement and draw attention to The Protocol on Environmental Protection to the Antarctic Treaty as a possible model for doing so.